Internal marketing and salespeople's out-of-role behaviour: The mediating role of job satisfaction - Ho Taek Yi; Yeonjin Cho; Fortune Edem Amenuvor (European Research on Management and Business Economics (ERMBE), 2023)
This study examines the effect of internal marketing (IM) on salespeople's in-role and out-of-role behaviours and how these behaviours affect customer satisfaction and sales performance. It also tests the mediating role of job satisfaction as an emotional response and adopts survey design. Data from 322 companies in Daegu and Gyeongbuk Province in the Republic of Korea are collected and used to test the conceptual model using structural equation modelling. The findings reveal that organisations' IM strategy for motivating employees positively affects salespeople's job satisfaction and out-of-role behaviour. The results also indicate that the salespeople's out-of-role behaviour enhances customer satisfaction and sales performance. This study suggests that organisations should provide guidelines and create an organizational culture that supports various IM activities to encourage employees' spontaneous behaviours. It is among the very few, if not the first, studies that demonstrate how companies' IM strategies could be leveraged to enhance job satisfaction and in-role and out-of-role behaviours in employees and how these behaviours could enhance customer satisfaction and sales performance.
Keywords: M30; M12; M51; L21; L25; 650; Internal Marketing; In-role behaviour; Out-of-role behaviour; Customer satisfaction